CONSUMER PERCEPTIONS OF BENEFITS AND BARRIERS OF QRIS IN COFFEE SHOP BUSINESSES - Ida Bagus Gede, Arsa Wedhana; Luh Putu , Mahyuni (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2023)
This study aims to empirically examine the factors that influence the intention or interest of coffee shop consumers to use QRIS in Denpasar, Bali. By understanding the factors that shape coffee shop consumer interest in using QRIS, it is hoped that the implications for business practices and policies will be more effective. Empirical data was collected by distributing questionnaires online involving 446 respondents and analyzed using SmartPLS3. This study provides empirical evidence that consumers' intention to use QRIS is positively and significantly influenced by perceived benefits and socialization. This study also found that socialization related to QRIS was positively and significantly influenced by perceived benefits and obstacles of QRIS, besides that the role of socialization was able to mediate perceptions of benefits on coffee shop consumer intentions in using QRIS. Perceived obstacles have a negative relationship to intentions, but both do not have a significant effect as well as the role of socialization which is unable to mediate between perceived QRIS barriers to intentions. This indicates that the benefits offered by QRIS with ongoing socialization regarding the benefits of QRIS are able to make consumers intend to use QRIS. The findings of this study have implications for policy makers to improve the security features of QRIS and increase socialization regarding the safety of using QRIS.